The diagnosis of consensus agreement in a MANET. (2017) - Chiang, Mao-Lun
For achieving the reliability, the fault tolerance of distributed systems needs to be studied. One of the most important problems of fault-tolerance issues is the fault diagnosis agreement (FDA). The goal of the FDA is to make each fault-free processor detect/locate a common set of faulty processors. However, previous works cannot solve the FDA problem in a mobile ad-hoc network (MANET). Therefore, the FDA problem is revised in this study by an evidence-based fault diagnosis protocol under dual failure characteristics on processors in a MANET. The proposed evidence-based mobile FDA protocol can detect/locate maximum number of faulty processors using minimum number of message exchange in a MANET.